(untitled) (Tamaddun, 2025)
This study was conducted to identify students’ learning styles, the problems they face, their strategies, and their perceptions of speaking English based on their respective learning styles. The research employed a descriptive qualitative approach. The tenth-grade Culinary A students of SMKN 2 Gowa were selected as the research subjects. Data were collected through observation, semi-structured interviews, and documentation. The results revealed that: (1) The most dominant learning styles employed by the students in the classroom is visual learning style, followed by auditory learning style and kinesthetic learning style (2) The problems experienced by students in English speaking activities based on their learning styles, such as visual learners faced issues such as lack of confidence, difficulty understanding instructions without visual aids, pronunciation challenges, and noisy classroom environments. Auditory learners encountered problems such as fear of making mistakes, confusion, discomfort, grammar issues, and hesitation, while kinesthetic learners struggled with boredom, panic, nervousness, lack of self-confidence, and fear of being laughed at. (3) The strategies identified by visual learners included planning, memorizing, taking notes, and preparing visual aids. Auditory learners resolved their difficulties by speaking loudly, watching video podcasts, memorizing, and using audio tools such as voice recordings, and kinesthetic learners addressed their challenges by asking for permission to move, using body movements, and employing physical tools such as pens or markers.